2018
DOI: 10.1108/ijccsm-07-2017-0160
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ perspectives

Abstract: Purpose Understanding farmers’ perceptions of how the climate is changing is vital to anticipating its impacts. Farmers are known to take appropriate steps to adapt only when they perceive change to be taking place. This study aims to analyse how African indigenous vegetable (AIV) farmers perceive climate change in three different agro-climatic zones (ACZs) in Kenya, identify the main differences in historical seasonal and annual rainfall and temperature trends between the zones, discuss differences in farmers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 68 publications
3
8
0
Order By: Relevance
“…Thus, farmers' perception appears to be in consonant with the statistical record of temperature from the meteorological station. This result is also in line with (Chepkoech et al 2018), who also found increasing trend in the temperature of study area.…”
Section: Farmers' Perception Of Change In Temperature Versus Meteorological Datasupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, farmers' perception appears to be in consonant with the statistical record of temperature from the meteorological station. This result is also in line with (Chepkoech et al 2018), who also found increasing trend in the temperature of study area.…”
Section: Farmers' Perception Of Change In Temperature Versus Meteorological Datasupporting
confidence: 92%
“…Unanimously, the farmers across the four States agreed that the UIVs' response to resultant effects of climate change differs and it is premised on the type of UIVs and season. This finding is in an agreement with Chepkoech et al (2018) who also found that the sensitivity of African Indigenous Vegetables to climate change variables is determined by the season and the type of vegetable, for instance, in the case of amaranth species, fluted pumpkin, jute mallow, and African eggplant; extreme rainfall does not really have effect on both their yield and the incident of insects and pests' infestations, although they experience moderate disease infestation such as yellowing of leaves. During the dry season, their yields are moderately low and moderate rate of pests and insects' infestation occur.…”
Section: Comparison Of Responses Of Uivs To Changes In Rainfallsupporting
confidence: 91%
See 3 more Smart Citations